Effect information technology and human resources on company performance with quality accounting information systems - Baihaqi Ammy (Jurnal Mantik, 2023)
The type of research conducted is quantitative research, which requires primary data in the form of respondents' perceptions (subjects) of research. The sample in this study were employees working at PT Pelindo Terminal Petikemas Belawan who were directly involved in the use of computers and accounting information systems with 40 respondents—data collection techniques based on questionnaires and interviews. Data analysis techniques The method used in this study is Structural Equation Modeling using partial least square (PLS) software. The research findings of information technology utilization have no effect on company performance, human resource competence affects company performance, information technology utilization has no effect on the quality of accounting information systems, human resource competence affects the quality of accounting information systems, the quality of accounting information systems affects company performance, information technology utilization has no effect on company performance with the quality of accounting information systems as an intervening variable, and human resource competence has no effect on company performance with the quality of accounting information systems as an intervening variable.